Bronchial inflammation in chronic bronchitis assessed by measurement of cell products in bronchial lavage fluid. - Riise, G. C. (1995)
BACKGROUND--Bronchial inflammation in chronic bronchitis has not been characterised as well as in asthma. The present study was undertaken to assess whether a characteristic pattern of bronchial inflammatory markers could be found in patients with chronic bronchitis. METHODS--Bronchoscopy with bronchial lavage was performed in 42 patients with chronic bronchitis and in 13 healthy controls. Twenty three of the patients had non-obstructive chronic bronchitis and 19 had chronic bronchitis and chronic obstructive pulmonary disease (COPD). Eighteen of the patients with bronchitis had recurrent infective exacerbations and 24 did not. Intrabronchial bacterial cultures were taken with a protected specimen brush. RESULTS--Increased activity of neutrophils, fibroblasts, and eosinophils was found in the patients with chronic bronchitis as assessed by the levels of myeloperoxidase (MPO) and interleukin-8 (IL-8), hyaluronan, and eosinophil cationic protein (ECP), respectively. The levels of tryptase did not differ from the controls. High correlations were found between the levels of MPO and IL-8, as well as ECP and IL-8. No differences were found between the patients with COPD and those with non-obstructive chronic bronchitis. CONCLUSIONS--Recruitment and activation of both neutrophils and eosinophils seem to be a characteristic of chronic bronchitis. This activation is associated with IL-8. The patients with intrabronchial cultures of Streptococcus pneumoniae had the highest individual levels of MPO, ECP, and IL-8 of all subjects in the study, indicating that colonisation with S pneumoniae could promote bronchial inflammation.